Investigation of the Performance of Thermal Energy Storage (TES) with Embedded Phase Change Materials (PCM) - Madhavan, Prasad (2018)
Thermal energy storage (TES) is an equipment utilized to store thermal or heat energy by means of sensible or latent heat storing methods with the aim of forming a poise between the energy production and utilization. Sensible TES with embedded phase change materials (PCM) as walls is has not been fully investigated. As a result, various design specification to measure performance improvement of a conventional TES has not been fully determined. Robust performance analysis and established the influence of design criteria for thermal energy storage with embedded walls of phase change materials is necessary to ensure the performance improvement of conventional TES. This study is conducted to experimentally investigate the performance of TES with embedded walls of PCM and to evaluate the influence of key parameters affecting the overall performance of the investigated TES. A Box-Behknken based Design of Experiment (DOE) is implemented for this study and it consists of various design parameters such as HTF mass flow rate, inlet temperature mass of embedded PCM. The results indicate that the performance of TES with embedded PCM is highly influenced by heat transfer fluid (HTF) inlet temperature, where an increase of HTF inlet temperature to 80oC, a value beyond the melting temperature of PCM, 60oC, increases the overall TES efficiency by at least 8% and increases the TES charging efficiency by 8%, however does not contribute significantly to TES discharging efficiency. TES discharging efficiency is greatly influenced by mass of PCM, where an increase of 1kg of PCM results to a drop of 15% in TES discharging efficiency for the investigated experimental set up. Mass flow rate investigated in this study shows a mild and inconsequential effect to any performance parameter. The TES with embedded PCM able to hold thermal energy for a duration of 62.4% longer than conventional TES.